Lights, camera, Amalee - Williams, Dar (New York Scholastic Press, 2006)
When seventh-grader Amalee uses an inheritance to make a movie about endangered species, she discovers a link with the mother she never knew
Hurg
5 8
Keywords: Endangered species -- Fiction; Interpersonal relations -- Fiction; Motion pictures -- Production and direction -- Fiction